A maiden's grave - Deaver, Jeffery (Viking, 1995)
A trio of desperate convicts has hijacked a bus carrying a group of deaf and mute schoolgirls who are now being held hostage in a disused slaughterhouse. FBI agent Arthur Potter has to negotiate with the men. The killers will murder one innocent child an hour until their demands are met.